EXPLORATION AND DEVELOPMENT OF DIGITAL-ETHICAL LEADERSHIP MODELS FOR SCHOOL PRINCIPALS IN EDUCATIONAL DECISION MAKING - Asmaul Husna; Endang Sri Maruti; Cerianing Putri Pratiwi; Supri Wahyudi Utomo (Universitas Labuhanbatu, 2026)
Purpose - This study aims to examine in depth and formulate a contextual and adaptive digital-ethical leadership model for school principals in the educational decision-making process.Methodology - This study uses an exploratory sequential mixed methods design with a naturalistic exploratory approach. Qualitative data were obtained through in-depth interviews with six elementary school principals in Bojonegoro Regency. In comparison, quantitative data were collected via a survey of three principals outside the research area to provide initial confirmation of the construct. Qualitative data analysis was conducted thematically using NVivo/ATLAS.ti, and quantitative data were analyzed descriptively using SPSS/R.Findings - The research findings demonstrate that digital-ethical leadership stems from a principal's capacity to integrate digital data with ethical dimensions while remaining sensitive to the school's sociocultural context. Technology is not positioned as the primary determinant of decisions, but rather as a supporting instrument guided by the values of justice, empathy, and moral responsibility.Contribution - The resulting model places ethics as the normative foundation in the digital transformation of education to produce equitable and sustainable decisions.